Legal Protection for Wives Who Are Victims of Domestic Violence - John Titus Ohoiner (Journal of Law Justice (JLJ), 2025)
This study aims to analyze the legal handling of wives as victims of domestic violence based on Law Number 23 of 2004 as lex specialis, as well as general criminal law provisions as lex generalis. Cases of domestic violence have shown a significant increase, including data reports and handling by the Women and Children Protection Unit of the Sorong City Police and the Sorong City Women's Empowerment and Child Protection Agency, which are authorized to conduct mediation. The research method used is empirical jurisprudence, combining literature study and field data to describe the form of legal protection and the effectiveness of its enforcement. The novelty of this research lies in mapping the patterns of handling domestic violence against wives in Sorong City by providing a comparative analysis between the application of Law 23/2004 and general criminal law, as well as linking it to the most dominant triggering factors, such as promiscuous behavior and excessive alcohol consumption. The results of this study show that although the legal framework has established clear protections, its implementation has not been optimal due to weak law enforcement and a lack of public education. The role of the government, particularly in legal counseling and prevention, has proven to be very influential in reducing the rate of violence. The conclusion of this study emphasizes that Law No. 23/2004 must be enforced consistently and firmly so that the protection of wives as victims can be effective and have a deterrent effect on perpetrators. Preventive efforts through education and social supervision also need to be strengthened to minimize domestic violence.